2021
DOI: 10.1371/journal.pone.0252942
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of income-related inequality in health check-ups services participation among elderly individuals across the 2008 financial crisis in Taiwan

Abstract: Encouraging citizens to use health checkup services is a health promotion strategy. In nations with aging populations, ensuring equitable use of health check-ups by senior citizens is a public health concern. The objective of this research was to quantify income-related inequality and its effect on the use of health checkup services in Taiwan during the 2007–2008 global financial crisis. We used the 2005 and 2009 datasets of the Taiwan National Health Interview Surveys to assess how income-related inequality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Health inequality is a systematic difference in the health status of different social groups. Many scholars have researched health inequality from multiple perspectives, such as income, social outcome, gender, and age [47][48][49][50][51]. Sentiments are a crucial aspect of mental health and are affected by various spatial environmental factors, resulting in health inequalities.…”
Section: Using Social Media Data To Study Sentiment Inequalitymentioning
confidence: 99%
“…Health inequality is a systematic difference in the health status of different social groups. Many scholars have researched health inequality from multiple perspectives, such as income, social outcome, gender, and age [47][48][49][50][51]. Sentiments are a crucial aspect of mental health and are affected by various spatial environmental factors, resulting in health inequalities.…”
Section: Using Social Media Data To Study Sentiment Inequalitymentioning
confidence: 99%
“…Nevertheless, undertaken preventive health check-ups has been influenced by a variety of sociodemographic and economic factors. Previous studies reported socioeconomic inequalities in undertaking health check-ups (14,15). Various socioeconomic inequalities may contribute to a difference in the uptake of preventive health check-ups (16).…”
Section: Introductionmentioning
confidence: 99%
“…They recommended promoting such service utilization among vulnerable groups to reduce inequality [17]. Chu et al analyzed the utilization of health examination service among the middle-aged and elderly in Taiwan during the 2007-2008 global financial crisis and found widespread income-related inequality, favoring the higher-income population [18]. Jens et al employed logistic regression models to analyze the factors affecting health examination service utilization among German residents.…”
Section: Introductionmentioning
confidence: 99%